2012
DOI: 10.1002/anie.201202455
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis and Biosynthetic Implications of (+)‐Fusarisetin A

Abstract: Starting from equisetin, the asymmetric synthesis of (+)-fusarisetin A has been accomplished in a one-pot transformation including a biomimetic oxidation and an intramolecular Diels-Alder/Roskamp reaction. Peroxyfusarisetin is proposed as a plausible biosynthetic intermediate based on studies of the oxidation of equisetin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 60 publications
(28 reference statements)
1
41
0
2
Order By: Relevance
“…We report herein the details of our synthetic studies of both equisetin ( 1 ) and (+)‐fusarisetin A ( 2 ) based on our proposed biosynthetic hypothesis. We previously demonstrated that oxidation of 1 with Mn(OAc) 3 /O 2 gave peroxyfusarisetin, which could be easily reduced to 2 4c. We now provide evidence that 1 and 2 should derive from the same biogenetic precursor: polyenoylamino acid 3 .…”
Section: Introductionmentioning
confidence: 53%
“…We report herein the details of our synthetic studies of both equisetin ( 1 ) and (+)‐fusarisetin A ( 2 ) based on our proposed biosynthetic hypothesis. We previously demonstrated that oxidation of 1 with Mn(OAc) 3 /O 2 gave peroxyfusarisetin, which could be easily reduced to 2 4c. We now provide evidence that 1 and 2 should derive from the same biogenetic precursor: polyenoylamino acid 3 .…”
Section: Introductionmentioning
confidence: 53%
“…16 The structures of these compounds were also confirmed by comparison with the known data. 16,17,24,31 …”
Section: Resultsmentioning
confidence: 63%
“…44 It is worth mentioning that, independently of this study, Gao et al recently reported the conversion of (−)-equisetin to (+)-fusarisetin A using Mn(III)/O 2 conditions. 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another nature-inspired synthesis of fusarisetin A has been reported by Gao et al [36,42], which is based on metal-promoted aerobic oxidation of equisetin.…”
Section: Synthesis Of Fusarisetin Amentioning
confidence: 99%